Campylobacter Cross‐Contamination of Chicken Products at an Abattoir. (20th June 2012) - Sasaki, Y.; Maruyama, N.; Zou, B.; Haruna, M.; Kusukawa, M.; Murakami, M.; Asai, T.; Tsujiyama, Y.; Yamada, Y.
Summary Consumption of raw or undercooked poultry products contaminated with Campylobacter has been identified as a risk factor for human campylobacteriosis. We determined whether slaughtering of Campylobacter‐positive flocks was associated with contamination of chicken products derived from Campylobacter‐negative flocks slaughtered at the same abattoir. The presence of Campylobacter was investigated in 22 broiler farms 1 week prior to slaughter and in one abattoir on nine separate slaughter days. A total of 600 bulk packed chicken products were tested, with 198 (33.0%) of the products found to be Campylobacter positive. Of the 350 chicken products originating from Campylobacter‐positive flocks, 180 (51.1%) were contaminated with the bacteria. In contrast, only 18 (7.2%) of 250 chicken products derived from Campylobacter‐negative flocks were contaminated. In 14 of these 18 products, the Campylobacter isolates were identical to isolates obtained from the flock slaughtered immediately prior to the Campylobacter‐negative flock. Notably, on 4/6 slaughter days, Campylobacter‐negative flocks were slaughtered prior to the positive flocks, and Campylobacter was absent from all chicken products originating from the negative flocks. These results suggest that implementation of logistic slaughter (where Campylobacter‐negative flocks are slaughter first) significantly decreases the prevalence of Campylobacter‐positive chicken products.